Analisis Penerima Bantuan Sosial menggunakan Bayesian Belief Network - Darfian Ardiansyah; Wildan Suharso; Gita Indah Marthasari (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Social Assistance is an expenditure in the form of money, goods, or services provided by the central or local government to protect the community from possible social risks, improve economic capacity, and the welfare of the community. In the welfare of society, there is a problem that is still unresolved to date, namely poverty. Poverty is an unresolved social problem in developing countries including Indonesia. In poverty itself, a person is declared poor if his opinion is lower than the poverty line and is unable to meet daily needs. From these problems, further analysis is needed to find the most influential criteria that can be used to maximize the program that has been made so that the economic level in the target household can increase. This research was conducted to analyze the factors that affect the change of economic level using Bayesian Belief Network method. From the scenario that has been done on the test using the Bayesian Belief Network method found that the increase in welfare and savings at community in the village of Srigading can increase the economic change up to 71%.